2019
DOI: 10.1097/rhu.0000000000001041
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Features of Systemic Vasculitides in the Southeast Region of Brazil

Abstract: Background/Objective The epidemiology of vasculitis is variable in different geographic areas, and this issue has not been approached in Brazil yet. The objective of this study was to assess the frequency of vasculitis in specialized centers in Brazil. Methods This cross-sectional study was performed in 9 vasculitis outpatient clinics from 6 different states mainly from the Southeast and the Northeast regions of Brazil between 2015 and 2017. Diagnosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 40 publications
5
29
1
9
Order By: Relevance
“…In the present study, only women were selected due to the higher prevalence of this gender in TAK [1,2]. Individuals over 50 years of age were excluded to minimize the inclusion of individuals with comorbidities inherent in older age groups, as well as patients with atherosclerosis and peripheral arterial disease [41], or other vasculitis such as giant cell arteritis [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, only women were selected due to the higher prevalence of this gender in TAK [1,2]. Individuals over 50 years of age were excluded to minimize the inclusion of individuals with comorbidities inherent in older age groups, as well as patients with atherosclerosis and peripheral arterial disease [41], or other vasculitis such as giant cell arteritis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Takayasu arteritis (TAK) is a primary systemic vasculitis characterized mainly by large-diameter vessels involvement, such as the aorta and major branches. Epidemiological studies have shown that the disease mainly affects women under the age of 40 years of age [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, it cannot be classified solely according to the caliber of the vessels involved, since it can affect small, medium, and large caliber vessels, in contrast to other types of systemic vasculitis, such as Takayasu's arteritis and giant-cell arteritis (which have a predilection for largecaliber vessels), polyarteritis nodosa and Kawasaki disease (with predilection for medium-caliber vessels), or antineutrophil cytoplasmic antibodies vasculitis (with a preference for small-caliber vessels). 9 The vascular form of the disease, vasculo-Behçet, is present in around 7 to 38% of cases and venous involvement is more common than arterial. 3,10 Arterial injuries have prevalence ranging from 3.6 to 31%, 3 generally develop in the aorta and pulmonary artery and their main branches, 11 and can vary from aneurysms to acute arterial thromboses or stenoses, most often affecting the renal, pulmonary, and abdominal arteries.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that it presents with nonspecific initial manifestations means that it may not by recognized by pediatricians and therefore recurrent oral ulcers at any phase of childhood or adolescence should be taken as a warning of the possibility of BD. 17 The disease has a very distinct geographical distribution, occurring predominantly in regions along the ancient "Silk Road", 9 running between Asia and the Mediterranean Basin, and it therefore affects many inhabitants of Japan, Iran, and Turkey. Prevalence is low in Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation